Authentic and Pragmatic Marketing Effects by Paradigm Shifts on Brand Authenticity to Produce Sustainable Value - Zohreh Ali Esmaeli; Bahram Kheiri; Farzin Farahbod (Indonesian Journal of Sustainability Accounting and Management, 2019)
This study aimed to investigate two marketing effects, namely, authentic and pragmatic, through paradigm shifts, as a solution to the epistemic crisis of brand authenticity. The research methods of this study were based on quantitative and descriptive surveys. The statistical population was 385 Iranian students at Islamic Azad Universities selected using stratified random sampling. The sample size was determined by Morgan’s table. Data were collected and distributed by questionnaire. The structural equation modeling technique used the partial least squares approach for data analysis. The findings indicate that both authentic and pragmatic marketing are more effective on brand authenticity through paradigm shift. Sustainable value production was not separate from economic growth. Rather, it sustains growth, and this paradigm shift, while developing the knowledge economy, affects the quality of a university-produced product. This makes it a prominent and authentic cultural institution, because brand originality has content in social interaction.